"Needed but lacked": Exploring demand- and supply-side determinants of access to cardiopulmonary resuscitation training for the lay public in China - Xuejie Dong; So Yeon Joyce Kong; Hanbing Xu; Andrew Fu Wah Ho; Andrew Fu Wah Ho; Andrew Fu Wah Ho; Audrey L. Blewer; Audrey L. Blewer; Tonje Soraas Birkenes; Helge Myklebust; Xiaojian Zheng; Minghua Li; et al. (Frontiers Media S.A., 2023)
BackgroundDespite years of public cardiopulmonary resuscitation (CPR) training efforts, the training rate and survival following out-of-hospital cardiac arrest (OHCA) have increased modestly in China. Access is imperative to increase the public CPR training rate, which is determined by both demand- (e.g., the lay public) and supply-side (e.g., CPR trainers) factors. We aimed to explore the demand and supply determinants of access to CPR training for the lay public in China.MethodsQualitative semi-structured interviews were conducted with 77 laypeople (demand side) and eight key stakeholders from CPR training institutions (supply side) in Shanghai, China. The interview guide was informed by Levesque et al. healthcare access framework. Data were transcribed, quantified, described, and analyzed through thematic content analysis.ResultsOn the demand side, the laypeople's ability to perceive their need and willingness for CPR training was strong. However, they failed to access CPR training mainly due to the lack of information on where to get trained. Overestimation of skills, optimism bias, and misconceptions impeded laypeople from attending training. On the supply side, trainers were able to meet the needs of the trainees with existing resources, but they relied on participants who actively sought out and registered for training and lacked an understanding of the needs of the public for marketing and encouraging participation in the training.ConclusionInsufficient information and lack of initiative on the demand side, lack of motivation, and understanding of public needs on the supply side all contributed to the persistently low CPR training rate in China. Suppliers should integrate resources, take the initiative to increase the CPR training rate, innovate training modes, expand correct publicity, and establish whole-process management of training programs.